Mixed infection with Porphyromonas gingivalis and Fusobacterium nucleatum in a murine lesion model: potential synergistic effects on virulence. - Feuille, F (1996)
These studies determined the characteristics of tissue destruction in a murine abscess model elicited by mixed infection with the periodontopathogens Fusobacterium nucleatum and Porphyromonas gingivalis. The interbacterial effects of this synergism, the kinetics of the relationship of the bacterial interaction, and the characteristics of the bacteria required for the tissue destruction were studied. Infection of mice with P. gingivalis and F. nucleatum strains elicited lesions of various sizes as a function of infective dose. Primary infection with F. nucleatum plus P. gingivalis at various ratios (i.e., <1:1) resulted in a significantly greater lesion size (P < 0.001) compared with that resulting from primary infection with P. gingivalis alone. At F. nucleatum/P. gingivalis ratios of > or = 1:1, spreading lesion formation and progression were significantly (P < 0.001) decreased, suggesting that bacterial interaction (i.e., coaggregation) may have inhibited the spread of the P. gingivalis infection to a site distant from the initial injection. Infection with F. nucleatum and P. gingivalis simultaneously (at different sites) or F. nucleatum administered within 4 h prior to or 1 h following P. gingivalis infection significantly enhanced the ability of P. gingivalis to form large phlegmonous lesions. Chemical inhibition of the P. gingivalis trypsin-like protease activity or the use of a trypsin-negative P. gingivalis strain abrogated tissue destruction either alone or in combination with F. nucleatum. Therefore, it was possible to examine aspects of virulence of these pathogens in a murine lesion model by either altering bacterial ratios, manipulating the time of infection, or targeting vital bacterial virulence factors.